A Novel Model-Free Control Technique for Angular Motion of Single Ducted-Fan Unmanned Aerial Vehicle - Tran Minh, Thien (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
This paper reveals the proposed method to operate landing angular motion of ducted-fan unmanned aerial vehicle (DUAV). The angular motion frequently varies during the landing stage. Additionally, the DUAV system is a complex system with uncertain parameters or incorrectly identified parameters, and the yaw angle has to be controlled in the proper position before grounding. Because of issues with structure of the system and identification in the real model of DUAV, a model-free control technique is approached by combining time-delay estimation (TDE) and integral sliding mode law (ISMC). Thanks to the TDE technique provides a model-free method for the complex system as DUAV. Hence, a novel control method is designed to achieve the desired angular motion. Besides, the ISMC method is a good solution for tracking performance. The stability of the whole system is guaranteed by the Lyapunov theory. The comparison between the TDE-ISMC and sliding mode control (SMC) is conducted in several cases to verify the effectiveness of the proposed TDE-ISMC control.